Remote Experiments, from Internet to Intranet - KOZÍK, Tomáš; KUNA, Peter; ŠIMON, Marek; ARRAS, Peter (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2015)
Remote experiments for teaching purposes are mediated by users, especiallyon the Internet. To access a remote experiment from within the universities, theintranet is also used. In terms of extending the application of remote experiments,an interesting method is the creation of community networks on the Internetwith associations of educational institutions. In this article authors focusedtheir attention on the formulation and application of remote experiments in education,in terms of their availability on the Internet and Intranet.